Synthesis of Phosphoramidate Prodrugs of Phenolic Natural Products and Drugs by Ester Exchange - Yao, Jie; Huang, Chengjie; Wu, Fan; Zhao, Yufen; Ni, Feng (Synthesis, 2022)
Drug development based on phenolic natural products as drug candidates against various diseases has gained much attention in recent years. However, most of those molecules lack therapeutic efficacy in clinical trials, usually due to poor bioavailability. Therefore, a prodrug approach was adopted to address the bioavailability problem of phenolic drugs. This paper describes a mild and convenient method for late-stage ProTide-type prodrug synthesis of phenolic pharmaceuticals, which gives various phosphoramidate prodrugs from unprotected phenolic natural products and drugs in high yield. More importantly, this reaction is amenable for the selective phosphorylation of the phenolic hydroxyl group in the presence of otherwise problematic nucleophilic functional groups like amines and alcohols. We also observed that the chemical release rate of the phenol can be substantially tuned by changing the amino acid residue on the phosphoramidate moiety.
Keywords: ProTide technology; prodrugs; phenolic drugs; phosphorylation; drug release; phosphoramidates